Slice encoding for the reduction of outflow signal artifacts in cine balanced SSFP imaging. Issue 4 (31st May 2021) - Ali, Fadil; Bydder, Mark; Han, Hui; Wang, Da; Ghodrati, Vahid; Gao, Chang; Prosper, Ashley; Nguyen, Kim‐Lien; Finn, J. Paul; Hu, Peng
Abstract : Purpose: Standard balanced SSFP (bSSFP) cine MRI often suffers from blood outflow artifacts. We propose a method that spatially encodes these outflowing spins to reduce their effects in the intended slice. Methods: Bloch simulations were performed to characterize through‐plane flow and to investigate how the use of phase encoding along the slice select's direction ("slice encoding") could alleviate its issues. Phantom scans and in vivo cines were acquired on a 3T system, comparing the standard 2D acquisition to the proposed slice‐encoding method. Nineteen healthy volunteers were recruited for short‐axis and horizontal long‐axis oriented scans. An expert radiologist evaluated each slice‐encoded/standard cine pairs in a rank comparison test and graded their quality on a 1‐5 scale. The grades were used for a nonparametric paired evaluation for independent samples with a null hypothesis that there was no statistical difference between the two quality‐grade distributions for α = 0.05 significance. Results: Bloch simulation results demonstrated this technique's feasibility, showing a fully resolved slice profile given a sufficient number of slice encodes. These results were confirmed with the phantom experiments. Each in vivo slice‐encoded cine had a higher quality than its corresponding standard acquisition. The nonparametric paired evaluation came to 0.01 significance, encouraging us to reject the null hypothesis and conclude that slice‐encoding effectively works in reducing outflow effects. Conclusion: The slice‐encoding balanced SSFP technique is helpful in mitigating outflow effects and is achievable within a single breath hold, being a useful alternative for cases in which the flow artifacts are significant.